Persepsi Siswa Terhadap Pelaksanaan Olahraga Renang Dari Segi Syari’at Islam di Aceh - Yulinar Yulinar; Suryani Suryani (Jurnal Dedikasi Pendidikan, 2018)
The sport of swimming is a sport which is performed in the water. In Aceh province, swimming is still not growing rapidly. Forward and backwards in the sport of swimming a lot of reasons that in the encounter as a minimal and tight clothing as well as a pool that still join between men and women raises controversial opinions and problems in the implementation of the sport of swimming. The pool is still a little difficult in still or can. Skimpy and tight clothing that does not fit the Islamic jurisprudence in Aceh. The purpose of the study is to know the perceptions of students against the implementation of sports swimming in terms of Islamic Sharia in Aceh province. The research methods included in the types of descriptive research. Samples taken were students of SMK, SMA and MAN. Data collection techniques with likert scale question form with the amount of grain as much as 56 grains. The analysis of the data by using a percentage of the research results. Based on research results in getting the perceptions of students need to be made of the pool as achievement, supporting sports achievements. Hope sports swimming can be a favorite sport in the province of Aceh. Swimsuit worn for swimming must comply with Islamic jurisprudence needs to be designed. It needs to be enforced separation of pools for swimmers of both men and women. Need for motivation against swimming sports to become one of the achievements that can bring the Province.  Results of the study the overall research retrieved from variables of students was 73% respond well to the sport of swimming. The results of the calculation of the appropriate pool sports statement against Islamic jurisprudence in aggregate can be 80% obtained very good.